2014
DOI: 10.1016/j.rgmxen.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive protein level in morbidly obese patients before and after bariatric surgery

Abstract: Background: Human obesity is associated with a proinflammatory state and an elevated level of mediators, such as C-reactive protein (CRP). Objectives: To establish CRP levels as baseline preoperative values and then at 6 months after bariatric surgery, as well as to determine the changes in weight, body mass index (BMI), leukocytes, and glycemia. Materials and methods: An observational, analytical, retrospective, longitudinal, and open study was conducted. Serum CRP values were measured in 36 adults presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Obesity has been associated with low-grade intestinal and systemic inflammation. In line with previous studies [27] we found a significant correlation between BMI and hsCRP. Moreover, hsCRP and TNF-α plasma levels were significantly higher in morbidly obese subjects compared with the controls in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Obesity has been associated with low-grade intestinal and systemic inflammation. In line with previous studies [27] we found a significant correlation between BMI and hsCRP. Moreover, hsCRP and TNF-α plasma levels were significantly higher in morbidly obese subjects compared with the controls in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, several parameters determined in our patient cohort were comparable to already established results from bariatric surgery patients including a massive drop of BMI, change in lipid profile including a drop in LDL and an increase in HDL and a reduction in inflammatory markers IL-6 and CRP and the prothrombotic protein PAI-1 [ 20 , 21 ]. Similar drops in weight and CRP levels were also described in a Mexican cohort of bariatric surgery patients [ 22 ]. The overall amelioration of obesity was further met by a reduction in medication needed.…”
Section: Discussionsupporting
confidence: 77%
“…103 Following a three-month low-calorie diet in healthy, obese women stratified into insulinresistant and insulin-sensitive groups, CRP concentrations were higher in the resistant group and correlated with insulin response; CRP decreased in parallel with weight loss in both groups 104 CRP levels are significantly lower in calorierestricted individuals when compared to those consuming an ad libitum Western diet. 105 CRP is consistently reduced in short-term and more extended time frames in VSG, [106][107][108] RYGB, 109,110 and AGB. 110 Hence, CRP has become a clinical biomarker of meta-inflammation.…”
Section: The Inflammation Of Obesitymentioning
confidence: 88%